Immunogenicity and efficacy of serogroup A and D bacterins against Pasteurella multocida in mice - Guan, Li-jun; Yang, Jin-qian; Xu, Qing-yuan; Feng, Yi-fan; Zhang, Xi-chen; Tang, Bo; Zhao, Zhan-qin (Frontiers in Veterinary Science, 2023)
Pasteurella multocida is a widespread respiratory pathogen in pigs, causing swine pneumonia and atrophic rhinitis, and the capsular bacterin serogroups A and D are the main epidemic serogroups in infected animals. This study investigated the protective effects of 13 serogroup A (seven A:L3 and six A:L6 strains) and 13 serogroup D isolates (all D:L6 strains) when injected as whole cell inactivated vaccines against homologous and heterologous P. multocida strains, to better understand the immunity generated by bacterins. All of the bacterins tested induced high titer levels of immunoglobulin G antibodies against the parental bacterial antigen in mice. Vaccination with the six A:L6 bacterins injected provided no protection against the parent strain, but some strains did provide heterologous protection against A:L3 strains. Vaccination with the seven A:L3 bacterins provided 50%–100% protection against the parent strain, but none gave heterologous protection against the A:L6 strains. Immunization with the thirteen D:L6 bacterins offered 60%–100% protection against the parent strain, and almost all D:L6 strains gave cross-protection. These results indicated that the cross-protectivity of serogroup A strains was poor, while serogroup D strains were effective.